2021
DOI: 10.4049/jimmunol.2100297
|View full text |Cite
|
Sign up to set email alerts
|

FcRn-Targeted Mucosal Vaccination against Influenza Virus Infection

Abstract: The respiratory tract is constantly exposed to various airborne pathogens. Most vaccines against respiratory infections are designed for the parenteral routes of administration; consequently, they provide relatively minimal protection in the respiratory tract. A vaccination strategy that aims to induce the protective mucosal immune responses in the airway is urgently needed. The FcRn mediates IgG Ab transport across the epithelial cells lining the respiratory tract. By mimicking this natural IgG transfer, we t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 60 publications
3
11
0
1
Order By: Relevance
“…immunized by S-Fc developed high levels of IgA Abs in the nasal washes and BAL. These results are consistent with the findings of previous studies where FcRn-targeted respiratory immunizations against viral mucosal infections 9, 28, 29 and adenovirus-vectored SARS-CoV-2 nasal vaccine 32, 33 elicit high Ab responses. In addition, the mice or hamsters i.m.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…immunized by S-Fc developed high levels of IgA Abs in the nasal washes and BAL. These results are consistent with the findings of previous studies where FcRn-targeted respiratory immunizations against viral mucosal infections 9, 28, 29 and adenovirus-vectored SARS-CoV-2 nasal vaccine 32, 33 elicit high Ab responses. In addition, the mice or hamsters i.m.…”
Section: Discussionsupporting
confidence: 93%
“…The FcRn-targeted nasal vaccine can be used for an unimmunized first dose or booster for those who have been immunized, even previously infected by SARS-CoV-2. The combination of mucosal and parenteral vaccines has been proven effective at mucosal entry against SARS-CoV-2 infections 7, 9, 44, 45 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At mucosal surfaces FcRn mediates pH-dependent transport of IgG antibodies and immune complexes (8,11,12), as well as albumin, which has an FcRn binding site that is distal and non-overlapping with that of IgG (13)(14)(15)(16). While studies have shown bidirectional transport of IgG and IgG Fc-fused antigens (17)(18)(19) in an FcRn-dependent manner, more recent studies have revealed a profound ability of albumin and albumin-fused antigens to cross epithelial cell barriers, followed by induction of antigen-specific antibody responses (20,21). This is highly interesting, as we have demonstrated that human albumin is transported more efficiently than IgG across mucosal surfaces after intranasal administration to human FcRn-expressing mice.…”
Section: Main Textmentioning
confidence: 99%